Reusable Iron/Iron Oxide-based Nanoparticles Catalyzed Organic Reactions - Adak, Laksmikanta; Kundu, Debasish; Roy, Keya; Saha, Malay; Roy, Anup (Current Organic Chemistry, 2022)
The last decade has witnessed a remarkable progress in the field of nanoscience and nanotechnology. Nanoparticles have been extensively used in diverse areas, including medicine, sensor, and catalysis. The easy accessibility of nanoparticles (NPs) with different shapes, sizes and compositions has inspired researchers to investigate their applications in catalysis. Recently, magnetic nanoparticles, such as iron-based nanoparticles, have attracted much consideration due to their unique properties, such as superparamagnetism, greater surface area, surface-to-volume ratio, and easy separation methodology. They increase the competence of organic reactions in terms of activity, selectivity, yield, simplicity, and sustainability. In this review, we focus on the developments of iron/iron oxide-based nanoparticles-catalyzed organic reactions and some examples of magnetic iron oxide nanoparticles as carriers/support for the main catalyst in organic reactions. Owing to magnetic properties, these nanocatalysts can be easily recovered from the reaction mixture by an external magnet and reused for several runs without loss of catalytic activity. Iron-based nanoparticles are used in a wide range of catalytic processes and applications. Notable focus has been on the hydrogenation of alkenes and alkynes, and also the hydrogenation of nitroarenes to aniline. Other catalyzed organic reactions, such as hydroboration of aldehydes and ketones, oxidative dehydrogenation of N-heterocycles, azide-alkyne cycloaddition reactions, synthesis of various heterocyclic compounds, multicomponent reactions, and crosscoupling reactions for C–C and C–heteroatom bond formation have been covered.
Keywords: Catalysis